2010
DOI: 10.1002/pssa.200925198
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of laser‐ and electric‐field‐induced effects on the crystallinity, surface morphology and plasmon resonance of indium and gold thin films

Abstract: The effects of post-deposition treatment of In and Au thin films by excimer laser and electric field are reported. The films were subjected to an electric field in the range of 0.1-3.3 kV/cm and laser irradiation in the range from 0.01 to 0.1 J/cm 2 . The effect of this treatment on the morphology and crystallinity of indium and gold thin films (10-100 nm thickness) is investigated. Indium films exhibited a three-fold grain growth at an electric field of 3.3 kV/cm. Gold thin film, on the other hand, showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Also, there will be a defined window for a particular laser parameter, for example laser fluence, which would provide suitable conditions. Laser processing is emerging as a powerful technique for material manipulation in general [70][71][72][73][74][75] and for carbon materials 76 in particular. Laserbased clean optical techniques therefore seem to have huge application potential for quick and scalable synthesis of impurity free 2D atomic sheets of graphene and its inorganic analogues.…”
Section: Rsc Advancesmentioning
confidence: 99%
“…Also, there will be a defined window for a particular laser parameter, for example laser fluence, which would provide suitable conditions. Laser processing is emerging as a powerful technique for material manipulation in general [70][71][72][73][74][75] and for carbon materials 76 in particular. Laserbased clean optical techniques therefore seem to have huge application potential for quick and scalable synthesis of impurity free 2D atomic sheets of graphene and its inorganic analogues.…”
Section: Rsc Advancesmentioning
confidence: 99%
“…It is observed that while the microstructural reconstruction of the surfaces can be manipulated, the amorphous–crystalline transition is irreversible [ 79 ]. Electric field–induced effects are having such substantial effects on grain size that it can work as a tool to play with the surface plasmonic modes of gold and indium [ 80 ]. For 50-nm-thin nickel film, electric field application has given rise to the growth of array of nickel nanodots (as shown in Fig.…”
Section: Guided Self-assemblymentioning
confidence: 99%
“…Moreover, the non-selectivity of a particular region for localized annealing is an issue as higher temperatures can damage the other nearby components, often leading to contamination and degradation of electrical performance [ 11 ]. Laser annealing is versatile and rapid; it offers precise and localized energy distribution to the material and is reported for Au films using continuous wave [ 12 ] and pulsed nanosecond lasers [ 13 , 14 ]. However, long, and short pulse interaction causes material melting, followed by a cooling and a re-solidification process [ 15 ].…”
Section: Introductionmentioning
confidence: 99%